UMKM menuju digitalisasi: Penyusunan laporan keuangan berbasis android Di Kota Prabumulih Provinsi Sumatera Selatan - Masnila, Nelly; Aprianti, Siska; Anugrah, Meilinda Dwi; Meilinda, Tiara; Rahmadi, Ideta Adelia; Rihan, Salsa Amanah Vintha (Penamas: Journal of Community Service, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in supporting the national economy. However, most MSME actors still face challenges in preparing systematic financial statements in accordance with accounting principles. Suboptimal financial management results in limited access to financing and hinders business development. Although Android-based devices are widely used, their utilization for financial recording and reporting remains relatively low. This community service activity is in partnership with the Bakoel Ibung MSME in Prabumulih City, which still records finances manually and has limited digital financial literacy. To address these challenges, this community service activity aimed to provide training on the use of an Android-based financial application, namely the Akuntansiku application, for Bakoel Ibung MSME. Through this activity, Bakoel Ibung MSME successfully implemented the Akuntansiku application in its daily business operations. Furthermore, the MSME demonstrated the ability to operate the application independently, starting from transaction input and account classification to the preparation of simple financial statements.